Mitigasi Bencana Abrasi Berbasis Keanekaragaman Vegetasi Mangrove di Pesisir Pantai Bagik Batu, Jerowaru - Irwansah, Irwansah; Usman, Usman; Muttaqin, Muh. Zaini Hasanul; Mahariyanti, Ermila (Jurnal Ilmiah Global Education, 2024)
Mangrove vegetation has an important role in maintaining the stability of coastal ecosystems in preventing abrasion. One of them is in the Bagik Batu Beach Coastal area, Jerowaru with various types of mangrove vegetation. This study aims to determine the density level of mangrove vegetation types in mangroves in abrasion mitigation on the coast of Bagik Batu Beach. The research uses the Belt Transect method. In each plot, 3 measuring plots were made, namely 10 x 10 m (for trees) with a diameter (20 ≤ DBH < 35 cm), 5 x 5 m (stakes) with a diameter (2 ≤ DBH < 20 cm), and 2 x 2 m (for seedlings) with a diameter (DBH < 2 cm). Based on the results of the study, 9 species of mangroves were found, namely 5 species of true mangroves (Major) and 4 species of mangroves (Minor), including; Avicennia alba, sonneratia alba, Rhizophora stylosa, Rhizophora apiculata, Calotropis gigantea, Lumnitzera racemosa, Jatropha gossypiifolia, Samanea saman and Azadirachta indica. Avicennia alba with the most species with the relative density of seedlings (39.68%), relative density of stakes (22.45%), relative density of trees (17.06%).